Does E-governance reduce income inequality in sub-Saharan Africa? Evidence from a dynamic panel - Toyo Amegnonna Marcel Dossou; Emmanuelle Ndomandji Kambaye; Mesfin Welderufael Berhe; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The ICT-income inequality relationship and the governance quality-income inequality nexus have been investigated in recent years. However, the moderating effect of ICT on the governance quality-income inequality linkage has been largely ignored. To fill this gap in the literature, this study examines the moderating effect of ICT on the relationship between governance quality and income inequality for a panel of 42 subSaharan African economies over the period 1996-2020. To achieve this goal, the generalized method of moments (GMM) estimation technique has been adopted. The results reveal that while ICT contributes to the improvement of income distribution, governance quality contributes to the exacerbation of income inequality. Interestingly, the results unveil that the promotion of E-governance could contribute to improve social welfare and reduce income inequality. ICT thresholds at which the positive incidence of governance on income inequality is completely nullified is 18.4 for governance effectiveness and 19.7 for regulatory quality. Policy implications are given based on the findings of this study.
Keywords: 330; ICT; governance quality; income inequality; GMM; sub-Saharan Africa